European cultural policy and culture management development of a common european cultural space - D.U. Zhyvohliadova, (Ukrainian Cultural Studies, 2018)
The article analyzes the potential of interaction between policy and management in the field of culture based on the experience of organizing and implementing cultural projects by the European Union. The purpose of the article is to analyze the EU experience in organizing and implement- ing the policy of developingthe common cultural space. Historical, systematic, comparative and typological methods of analysis are used. The main conclusions are: European Union culture managerial experience demonstrates certain productive results as well as the possibilities of optimizing the activities of the relevant institutes, methods and mechanisms for the implementation of cultural policy. This productivity is determined by an effort to maintain a correlation between the theoretical and practical levels of political activity in the field of culture and, therefore, through specific programs, to support and develop all sectors of culture.
Keywords: European Union, cultural policy, management, cultural space, cultural programs